The Effectiveness of using the Biofilter made from Bidara (Sidr) to reduce the negative effects of Mice Cigarette Smoke - Mulyono, Agus (Iraqi Journal of Science, 2023)
This study aims to determine the effect of exposure to cigarette smoke with a biofilter of bidara leaf powder on the histology of the liver, lungs and blood viscosity of mice. This test was carried out for 28 days by giving cigarette smoke with a biofilter of bidara leaf powder and observing the histology of the liver, lungs and blood viscosity. The results showed that exposure to cigarette smoke with a biofilter of bidara leaf powder was very effective in reducing damage to the liver and lungs of mice, and also very effective in reducing blood viscosity as in normal mice blood viscosity. The use of Bidara leaf powder biofilter can affect the histology of the liver, lungs and blood viscosity in mice. Bidara leaf powder biofilter can minimize the negative impact of cigarette smoke.